2009
DOI: 10.1080/01638530902959638
|View full text |Cite
|
Sign up to set email alerts
|

Referencing in a Second Language: Korean EFL Learners' Cohesive Use of References in Written Narrative Discourse

Abstract: This study examined Korean English as a foreign language (EFL) learners' ability to establish textual cohesion in English through appropriate selection of reference forms and reference management strategies in their written narrative discourse. It employed both quantitative and qualitative analysis to explore how the languagespecific reference choices and strategies in their first language (L1) may be evident in their second language (L2) discourse production. Participants were Korean adult EFL learners and Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 19 publications
3
27
0
Order By: Relevance
“…Kang (2004) similarly showed how Korean EEL learners' English narratives were less coherent and cohesive than the native English speakers' due to the specifically Korean linguistic strategy of relying on nomináis in place of pronominals in marking anaphoric references. Kang (2009) further illustrated how such LI-specific strategies, in combination with the lack of L2 linguistic competence, prevented Korean EFL learners from achieving discourse effects through sophisticated use of referential strategies in their narrative production. Chen and Pan (2009) similarly found that Chinese-English bilinguals' LI practice in the use of referential expressions hindered the development and appropriate use of the same language functions in English.…”
Section: Backgroundsmentioning
confidence: 98%
See 1 more Smart Citation
“…Kang (2004) similarly showed how Korean EEL learners' English narratives were less coherent and cohesive than the native English speakers' due to the specifically Korean linguistic strategy of relying on nomináis in place of pronominals in marking anaphoric references. Kang (2009) further illustrated how such LI-specific strategies, in combination with the lack of L2 linguistic competence, prevented Korean EFL learners from achieving discourse effects through sophisticated use of referential strategies in their narrative production. Chen and Pan (2009) similarly found that Chinese-English bilinguals' LI practice in the use of referential expressions hindered the development and appropriate use of the same language functions in English.…”
Section: Backgroundsmentioning
confidence: 98%
“…The research attention to such different aspects of narrative production reflects the complex multidimensional nature of narrative production that requires a range of cognitive capacities as well as linguistic and pragmatic knowledge, as one not only needs knowledge of how to use formal linguistic devices to serve specific communicative functions, but also needs pragmatic sensitivity to the listeners' needs, while displaying social and cultural knowledge of cultural values to interpret different events and characters at the same time. Most past studies of narratives have examined the two dimensions of narratives separately (Akinci, Jisa & Kern, 2001;Hickmann, 1996a), and identified developmental and culture-and language-specific characteristics of each of the two main dimensions of narrative production (Hickmann & Hendricks, 1999;Kang, 2009;Minami, 2002;Ordonez, 2000;Peterson & McCabe, 1983). …”
Section: Introductionmentioning
confidence: 98%
“…Given the difficulties outlined above when acquiring bridging in L2, a variety of studies from the East-Asian L2 English context have confirmed that L2 learners from Asian language backgrounds are unable to properly maintain L2 English target norms of syntax-pragmatic reference marking in L2 narrative production (Hendriks, 2003;Kang, 2005Kang, , 2009Ryan, 2012Ryan, , 2015Ryan, , 2016Crosthwaite, 2013;2014a, 2016b. These studies look at the breadth of referring expressions produced by Asian learners of L2 English including zero, pronominal and full NP reference, using narrative picture descriptions or film retellings as the elicitation device.…”
Section: Acquiring Bridging In L2mentioning
confidence: 99%
“…Research on cohesion has been especially fruitful as cohesive devices can be explicitly traced or observed on the surface. What has emerged out of this line of research is that L2 writers often underuse, overuse, and misuse certain types of cohesive devices (Bolton, Nelson, & Hung, 2003;Granger & Tyson, 1996;Hinkel, 2001;Kang, 2009). Bolton et al (2003) and Granger and Tyson (1996) focused on the use of sentence transitions such as however, therefore, and for example.…”
Section: Coherence and Cohesion In L1 Vs L2 Textsmentioning
confidence: 99%
“…Other studies focused on different sub-groups of cohesive devices, including contrastive conjunctions such as but and yet (e.g., Park, 2013), conjunctive adjuncts including conjunctions and conjunctive adverbials (e.g., Yoon & Yoo, 2011), and reference (e.g., Kang, 2009;Kim, 2012). Park (2013) examined Korean college EFL students' use of contrastive conjunctions in argumentative essays and found that the nonnative speakers overused and underused certain contrastive conjunctions compared to the native control group.…”
Section: Coherence and Cohesion In L1 Vs L2 Textsmentioning
confidence: 99%